Ultrasonografic changes in the axillary vein of patients with lymphedema after mastectomy - Gilberto Ferreira de Abreu Junior; Guilherme Benjamin Brandão Pitta; Marcelo Araújo; Aldemar de Araújo Castro; Walter Ferreira de Azevedo Junior; Fausto Miranda Junior (Revista do Colégio Brasileiro de Cirurgiões)
OBJECTIVE: To determine the prevalence of sonographic abnormalities (SA) in the axillary vein of patients with and without post-mastectomy lymphedema. METHODS: We studied a sample of 80 women, divided into two equal groups, with and without lymphedema, with B mode ultrasound, color and pulsed Doppler. The primary variable, SA, is defined as change in the venous diameter, parietal thickening, intraluminal images, compressibility, parietal collapse at inspiration and feature of the axillary venous flow on the operated side. Secondary variables were: stage of lymphedema, surgical technique, number of radio and chemotherapy sessions, limb volume, weight and age. The differences between the proportions in the groups were determined using the Chi-square test and / or Fisher's test. For continuous variables, we used the Mann-Whitney Test. To estimate the magnitude of the associations, we used the prevalence rate of SA in both groups as a measure of frequency, and as a measure of association, the prevalence ratio (PR) obtained as a function of relative risk (RR) and estimated by the test Mantel-Haenszel homogeneity test. We adopted the statistical significance level of 5% (p < 0.05). RESULTS: only the criterion "parietal thickening" was strongly associated with the lymphedema group (p = 0.001). The prevalence of SA was 55% in patients with lymphedema and 17.5% in the group without it, with difference in prevalence of 37.5%. CONCLUSION: the prevalence of SA was higher in patients undergoing mastectomy with lymphedema than in those without lymphedema.